1984
DOI: 10.1071/wr9840491
|View full text |Cite
|
Sign up to set email alerts
|

The Food of Fox, Dog and Cat in Croajingalong National Park, South-Eastern Victoria.

Abstract: The diet of foxes, dogs and cats living in Croajingalong National Park in extreme south-easten Victoria was studied during 1979 and 1980. From 1397 scats collected over 20 months, remains of 22 indigenous and 7 introduced mammal species were identified. Remains of ringtail possums Pseudocheirus peregrinus predominated in the scats from all three predators (fox 58%, cat 56% and dog 38%). Other main prey species for the fox and cat were Antechinus spp.(24% and 15% respectively) and Rattus spp. (15% and 19%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 0 publications
5
60
0
Order By: Relevance
“…Cats differ from canids in several ways: (i) they have a partially arboreal habit; (ii) they have excellent night vision, unlike the canids, which rely heavily on their highly developed olfactory senses; (iii) when live prey are available, they do not require water (Jones 1988;Newsome 1991); (iv) they prey more heavily upon birds and reptiles than do the canids (Bayly 1978;Triggs et al 1984;Catling 1988;Lumsden et al 1991), although the avian component of the diet is still considered to be minimal (Coman 1973(Coman , 1991Jones 1992); and (v) they appear to be more selective in their choice of prey than are canids (Bayly 1978). Unlike canids, cats are generally not scavengers (Bayly 1978;Jones and Coman 1981).…”
Section: Felis Catusmentioning
confidence: 99%
See 3 more Smart Citations
“…Cats differ from canids in several ways: (i) they have a partially arboreal habit; (ii) they have excellent night vision, unlike the canids, which rely heavily on their highly developed olfactory senses; (iii) when live prey are available, they do not require water (Jones 1988;Newsome 1991); (iv) they prey more heavily upon birds and reptiles than do the canids (Bayly 1978;Triggs et al 1984;Catling 1988;Lumsden et al 1991), although the avian component of the diet is still considered to be minimal (Coman 1973(Coman , 1991Jones 1992); and (v) they appear to be more selective in their choice of prey than are canids (Bayly 1978). Unlike canids, cats are generally not scavengers (Bayly 1978;Jones and Coman 1981).…”
Section: Felis Catusmentioning
confidence: 99%
“…Although rabbits appear to be a preferred prey item (Bayly 1978;Jones and Coman 1981;Catling 1988), cats are known to consume individuals of 2-3 native animal species per day even where rabbits are abundant (Paton 1993). Where rabbits are often scarce, such as in forest environments, native species such as the ringtail possum (Pseudocheirus peregrinus) and the bush rat (Rattusfuscipes) can become important prey (Jones and Coman 1981;Triggs et al 1984).…”
Section: Felis Catusmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have found that dogs and foxes take different sized mammalian prey (e.g., Triggs et al 1984;Brunner and Wallis 1986;Brown and Triggs 1990). This general finding did not apply to Mumbulla State Forest in 1981-2 but it did apply in 1996.…”
Section: Discussionmentioning
confidence: 97%